Selected aspects of manufacturing and strength evaluation of porous composites based on numerical simulations - Wiesław Frącz; Grzegorz Janowski; Grażyna Ryzińska (Advances in Mechanical and Materials Engineering, 2017)
In this paper the numerical simulations of microcellular injection molding process for polymer composite with glass fiber for variable content of pores were carried out. In order to evaluate the strength of the three-phase composite structure (polypropylene PP as a matrix, 20% wt. of glass fiber GF and 1-9 % vol. of the pores) a microstructural analysis was performed and strength calculations were conducted using the Mori-Tanaka homogenization model. The analyzed product (the base of industrial mop) was subjected to the loading in Ansys 14.5 commercial code, considering the impact of pores content on its mechanical properties. Furthermore, the paper presents the visualization of calculated composite microstructure for variable pores contents.